Mechanical and durability characteristics of multiwalled carbon nano tube in concrete. Issue 1 (June 2020) - Rashmi, R; Padmapriya, R
Abstract: Concrete is the widely used reliable constructions material worldwide in the field of Civil Engineering with various reforms using advanced Technology. One of the encroachments is the Nano science and it has also played a remarkable role in the field of material science. Eventually Nano materials were used in the concrete to intervene new material at Nano scale and thereby increasing the Mechanical, Chemical and durability property. Various Nano materials are being used in civil Engineering, off all those Nano materials used in the concrete are Nano silica, Multi walled Carbon Nano tubes, and Nano Titanium oxide. These Nano materials are used in producing High performance concrete which exhibits tremendous strength and durability of concrete. The material that is used in this research paper is Carbon Nano tubes. The multiwalled carbon Nano tubes exhibits exceptionally high Mechanical Property and also act as a reinforcing material for the high performance concrete. These multiwall carbon Nano tubes are effectively incorporated in concrete by ultrasonic method and using surfactant. There are interfacial interactions between carbon nanotubes and the hydrations of cement, which enhances a high bonding strength between the reinforcement and cement matrix. Mutiwalled carbon nanotubes are various ratio is incorporated with the concrete of mix proportion M40 grade of concrete. Their mechanical property is thereby compared with the nominal concrete mix. In this research the fine aggregate is also partially to fully replace by manufactured sand as the demand for the river sand is high, an alternate is sought. Besides the mechanical property and the complex reinforcement of cement matrix, the Nano concrete exhibits early strain capacity which shows a considerable improvement in the long term durability of the concrete.